Leptospirosis-induced transverse myelitis and multiorgan failure: an uncommon manifestation in non-epidemic setting - Gul, Muhammad Hamza; Siddiqui, Aisha; Siddiqui, Farina Fatima; Ahmad, Waqas; Wardak, Abdul Baseer; Oza, Yugam Rajeshkumar (International Journal of Scientific Reports, 2024)
Leptospirosis is a disease that can be transmitted from animals to humans. It is caused by a bacterium called Leptospira interrogans and is more common in tropical and subtropical regions. Despite being the most neglected tropical disease, it is a significant emerging and re-emerging disease, according to recent reports and reviews by the World Health Organization (WHO). Leptospirosis is widespread among humans and animals globally, and it is estimated that there are 1.03 million cases and 58,900 deaths annually, with a case fatality rate of 6.85%. Acute transverse myelitis (TM) is a rare neurological disease that affects the spinal cord. It is caused by various autoimmune reactions and is usually limited to several spinal cord segments. It has a poor prognosis. Our case report presents a unique situation where a patient developed multiorgan failure due to leptospirosis and also had a rare co-presentation of transverse myelitis.